Media Exposure, Tipe Industri, Profitabilitas, dan Ukuran Perusahaan Terhadap Carbon Emission - Rosyid, Rosyid; S.A.Immawati (MAMEN: Jurnal Manajemen, 2022)
This study aims to examine the factors that influence the disclosure of carbon emissions. Factors tested in this study include media exposure, industry type, profitability, and company size. The method used to measure the extent of disclosure of carbon emissions adopts a check list developed based on request sheets obtained from the Carbon Disclosure Project (CDP). The research sample was selected using purposive sampling and selected 10 mining companies and goods and service industries listed on the Indonesia Stock Exchange starting from 2018-2020. The data analysis technique uses panel data regression with eviews software version 10. The panel data regression results that are more appropriate to use are the Random Effect Model (REM) because it is better at estimating the independent variables on the dependent variable. The results of the data analysis show that media exposure and the ratio of debt to equity have a significant negative effect on the disclosure of carbon emissions, while the factors of industry type and company size have a positive effect on the disclosure of carbon emissions. Where the rise and fall of earnings quality can be explained by the independence variable in this study of 62.6 percent.